Identifikasi Kecelakaan Kerja Menggunakan Metode JSA (Job Safety Analysis) di PT Kanaan Global Indonesia - Sabrina Salsabila; Erna Indriastiningsih; Anita Oktaviana Trisna Devi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study was conducted to analyze the causes of occupational accidents and to identify potential hazards in the material cutting process at PT Kanaan Global Indonesia using the Job Safety Analysis (JSA) approach. The high number of occupational accidents, totaling 15 cases during the period of December 2024–May 2025, indicates the existence of gaps in occupational safety control in this area. Data were collected through direct observation, interviews with workers, and the collection of historical data from the Occupational Health and Safety (OHS) unit. Risk analysis was carried out using a risk matrix to determine likelihood and severity values, followed by JSA for each work stage. The results identified 25 potential hazards, consisting of 4 risks in the extreme category, 9 in the high category, 7 in the medium category, and 5 in the low category. High-risk hazards were predominantly found in roll cutting and cutting press machines, which are characterized by mechanical hazards. Control recommendations focus on the implementation of engineering controls such as the installation of guarding systems and safety light curtains, improvements in safe work procedures, and increased discipline in the use of personal protective equipment (PPE). These findings demonstrate that the JSA method provides a comprehensive overview of risk sources and serves as an effective basis for formulating occupational accident control strategies within the company.